Morte e immortalità digitale: la vita dei dati online e l’interazione postuma - Sisto, Davide (Funes. Journal of narratives and social sciences, 2018)
In this essay, I try to tackle some of the most relevant topics concerning the so-called Digital Death. In particular, I try to highlight how our relationship with death has been changing with the spread of digital culture. The core concept of “posthumous interaction” allows us to understand when data can be said to be “alive” or “dead”. The starting point is the distinction between biological life and digital life in all individuals. From here we can make some fundamental considerations about two concepts that are very important nowadays: digital legacy and digital immortality. The analysis of these two concepts allows us to understand that it is now impossible to grasp the social and cultural meaning of death without considering the influence of digital culture on the way we live in this world.